1993
DOI: 10.1021/ba-1993-0233.ch014
|View full text |Cite
|
Sign up to set email alerts
|

Rubber-Modified Epoxies

Abstract: The phase-separation process of a diepoxide based on bisphenol A diglycidyl ether cured with a cycloaliphatic diamine in the presence of an epoxy-terminated butadiene-acrylonitrile random copolymer (ETBN) was experimentally studied and theoretically simulated. The increase in the average molecular weight of the epoxy-amine polymer is shown to be the main thermodynamic factor leading to phase separation. The competition between nucleation-growth and spinodal decomposition is analyzed. Low values of interfacial … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

1997
1997
2000
2000

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 43 publications
(15 citation statements)
references
References 23 publications
0
15
0
Order By: Relevance
“…ment obtained was much lower than those obAs deduced from these figures and also from Table tained for other rubber-containing epoxy mix-V, there were essentially no discernable differtures. 2,5 This was possibly a consequence of a poor ences between the morphologies of these mixprereaction between the mixed compounds. We wish to analyze these different casting possibilitures.…”
Section: Resultsmentioning
confidence: 99%
“…ment obtained was much lower than those obAs deduced from these figures and also from Table tained for other rubber-containing epoxy mix-V, there were essentially no discernable differtures. 2,5 This was possibly a consequence of a poor ences between the morphologies of these mixprereaction between the mixed compounds. We wish to analyze these different casting possibilitures.…”
Section: Resultsmentioning
confidence: 99%
“…The reaction then slows and finally ceases before all of the monomer has been consumed. The cessation of polymerization prior to Effect of Cure Temperature total monomer consumption has been widely observed in the cure of glass-forming networks 23,26,29 To further investigate the curing kinetics, the vinyl ester resin was isothermally cured at a range and is due to diffusion control of the curing process when the glass transition temperature (T g ) of temperatures but with constant initiator concentration. Figure 7 shows the rate as a function approaches the curing temperature (T cure higher curing temperatures, the final degree of of reaction (over a period of 6 h).…”
Section: May Bementioning
confidence: 99%
“…Cloud-point temperature increase, for a given composition of RLP/epoxy prepolymer, with the cess, an opposite effect should be observed. This mean molar mass of the epoxy was analyzed leads to believe that residence time evolution in by Verchere et al 9 They reported for a CTBN reactive extrusion is too complex to be examined 1 8/epoxy prepolymer blend that an increase of using only the nonreactive twin-screw extrusion the epoxy prepolymer molar mass from 349 to 383 modeling. grmol 01 leads to an increase of the precipitation temperature of 14ЊC.…”
Section: Resultsmentioning
confidence: 99%